What role for citizens? Evolving engagement in quadruple helix smart district initiatives - Davies, Anna (My University, 2023)
Globally, smart city initiatives are becoming increasingly ubiquitous elements of complex, sociotechnical urban systems. While there is general agreement that cities cannot be smart without citizen involvement, the motivations, means, and mechanisms for engaging citizens remain contested. In response, this article asks what the role of citizens is in two recently established smart districts within the wider Smart Dublin programme: Smart Sandyford, a business district, and Smart Balbriggan, a town north of Dublin with Ireland’s most ethnically diverse and youthful population. Using multiple methods (online and in-person interviews, site visits, a focus group, and participant observation), this article specifically examines how the “quadruple helix,” a popular concept within innovation studies and one that is adopted in promotional materials by Dublin’s emerging smart districts, is used by key actors as an overarching framing device for activities. It finds that, to date, the quadruple helix concept is being applied simplistically and uncritically, without attention to pre-existing and persistent patterns of uneven power and influence between the different actors involved. As such it risks inhibiting rather than supporting meaningful citizen engagement for smart and sustainable places that both smart districts articulate as a key driver of their activities.
PUBLISHED
Keywords: Citizen engagement; Dublin; Hackathon; Ireland; Quadruple helix; Smart cities; Smart districts; Digital Engagement; Inclusive Society; Smart Cities